2012
DOI: 10.1186/1758-3284-4-21
|View full text |Cite|
|
Sign up to set email alerts
|

Reconstruction of scalp defects with the radial forearm free flap

Abstract: BackgroundAdvanced and recurrent cutaneous squamous cell carcinoma of the scalp and forehead require aggressive surgical excision often resulting in complex defects requiring reconstruction. This study evaluates various microvascular free flap reconstructions in this patient population, including the rarely utilized radial forearm free flap.Patients and methodsA retrospective review of patients undergoing free flap surgeries (n = 47) of the scalp between 1997 and 2011 were included. Patients were divided prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…As reported in the literature, most scalp reconstructions use a latissimus dorsi free flap (49% n = 280/567), followed by rectus abdominis (17% n = 96/567) and anterolateral thigh (14% n = 77/567) free flaps. The radial forearm free flap is less frequently reported at 8% (n = 44/567) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in the literature, most scalp reconstructions use a latissimus dorsi free flap (49% n = 280/567), followed by rectus abdominis (17% n = 96/567) and anterolateral thigh (14% n = 77/567) free flaps. The radial forearm free flap is less frequently reported at 8% (n = 44/567) …”
Section: Discussionmentioning
confidence: 99%
“…Radial forearm free flap confers various advantages over other free flap options. Sweeny et al reported that RFF resulted in shorter duration of hospitalisation and fewer complications requiring surgical intervention. This study adds to the literature by showing that radial forearm free flaps heal significantly faster at 16 days on average, compared to latissimus dorsi at 34 days.…”
Section: Discussionmentioning
confidence: 99%
“…4,25 The advent of reconstructive microsurgery has allowed single stage, complete scalp reconstruction using distant tissue, and can be performed at the time of tumor extirpation. Consequently, numerous free flaps have been described for scalp reconstruction, including free omentum flap with skin graft, 26,27 groin flap, 1 LD muscle or musculocutaneous flap, 7-10 radial forearm flap, [28][29][30][31] rectus abdominis flap 19 and ALT flap. [16][17][18]32 The advantages and disadvantages of free flaps used in the coverage of scalp defects are listed in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Although the success rate of free tissue transfers for head and neck soft tissue reconstruction has greatly improved, soft tissue reconstruction involving the scalp and forehead remains challenging . Most of the existing literature on free tissue reconstruction of the scalp and forehead involves reconstructing soft tissue defects resulting from cutaneous malignancy excision, without the need for implant coverage or salvage . St‐Hilaire et al reported salvaging failed cranioplasty with nonanatomic titanium mesh and perforator flap, but all previously placed implants had to be removed.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Most of the existing literature on free tissue reconstruction of the scalp and forehead involves reconstructing soft tissue defects resulting from cutaneous malignancy excision, without the need for implant coverage or salvage. [19][20][21][22] St-Hilaire et al 23 reported salvaging failed cranioplasty with nonanatomic titanium mesh and perforator flap, but all previously placed implants had to be removed. The purpose of this study was to share the authors' experience in salvage of postcranioplasty implant exposure utilizing free tissue transfer, without the need to remove previously placed implant in the majority of the cases.…”
mentioning
confidence: 99%